Gaya Kepemimpinan Dan Budaya Organisasi: Pengaruhnya Terhadap Kinerja Karyawan - Asmawiyah _ (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2019)
This study aims to determine the influence of leadership style and organizational culture on the performance of employees of PT. Japfa Comfeed Indonesia, Tbk Makassar Unit. The research model used in this study is the method of observation, interviews, questionnaires, and literature studies conducted systematically based on the research objectives. The sample in this study is 95 respondents. The analytical method used is multiple linear regression analysis, coefficient of determination analysis (R2), T test (partial) and F test (simultaneous). The results of the study show that leadership styles have a positive and significant influence on employee performance while organizational culture has a positive but not significant effect on employee performance. This makes the leadership style the most dominant variable affecting the performance of employees at PT. Japfa Comfeed Indonesia, Tbk Makassar Unit.